IN VITRO ANTIOXIDANT ACTIVITIES OF THE FRACTIONS OF COCCINIA GRANDIS L. LEAF EXTRACT - Umamaheswari, M.; Chatterjee, T. K. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
The present study was aimed at investigating the antioxidant activities of the various fractions of the hydromethanolic extract of the leaves of Coccinia grandis L. Voigt. (Cucurbitaceae). The antioxidant activities of the fractions have been evaluated by using nine in vitro assays and were compared to standard antioxidants such as ascorbic acid, α-tocopherol, curcumin and butylated hydroxyl toluene (BHT). All the fractions showed effective H-donor activity, reducing power, free radical scavenging activity, metal chelating ability and inhibition of β-carotene bleaching. None of the fractions exerted an obvious pro-oxidant activity. The antioxidant property depends upon concentration and increased with increasing amount of the fractions. The free radical scavenging and antioxidant activities may be attributed to the presence of phenolic and flavonoid compounds present in the fractions. The results obtained in the present study indicate that the leaves of C. grandis are a potential source of natural antioxidant.